Oxi-Inflamm-Aging: a New Theory with Practical Implications - Ángel Julio Romero Cabrera; Leocadia Amores Hernández (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2016)
Oxidative stress causes an impairment of the physiological systems essential for maintaining homeostasis, including the immune system. Immune dysregulation leads to a chronic low-grade inflammatory state in aging. This is the basis of the new integrative theory called oxy-inflamm-aging. The present article describes the foundations of this theory, the current research studies that support it, and its link with the pathogenesis of some age-related diseases. It is concluded that the adoption of a healthy lifestyle from an early age can contribute to a successful aging. The benefits of caloric restriction and antioxidant supplements are still under study in order to prevent oxidative stress and inflammation, and consequently achieve greater longevity and reduce the burden of age-associated diseases.